2010
DOI: 10.1016/j.ajhg.2010.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in SCARF2 Are Responsible for Van Den Ende-Gupta Syndrome

Abstract: Van Den Ende-Gupta syndrome (VDEGS) is an extremely rare autosomal-recessive disorder characterized by distinctive craniofacial features, which include blepharophimosis, malar and/or maxillary hypoplasia, a narrow and beaked nose, and an everted lower lip. Other features are arachnodactyly, camptodactyly, peculiar skeletal abnormalities, and normal development and intelligence. We present molecular data on four VDEGS patients from three consanguineous Qatari families belonging to the same highly inbred Bedouin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
52
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(57 citation statements)
references
References 24 publications
5
52
0
Order By: Relevance
“…deletion in our patient was surprising. The recent identification of homozygous mutations in the SCARF2 gene in inbred families with VDEGS [Anastasio et al, 2010] suggested unmasking of a recessive mutation of SCARF2, which is located within the 22q11.2 common deletion region. Subsequent sequencing of SCARF2 in our patient revealed indeed a maternally inherited splice site mutation in addition to the 22q11.2 microdeletion and hence absence of a functional SCARF2 gene.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…deletion in our patient was surprising. The recent identification of homozygous mutations in the SCARF2 gene in inbred families with VDEGS [Anastasio et al, 2010] suggested unmasking of a recessive mutation of SCARF2, which is located within the 22q11.2 common deletion region. Subsequent sequencing of SCARF2 in our patient revealed indeed a maternally inherited splice site mutation in addition to the 22q11.2 microdeletion and hence absence of a functional SCARF2 gene.…”
Section: Discussionmentioning
confidence: 99%
“…SCARF2 contains putative epidermal growth factor-like domains in its extracellular domain, along with a number of positively charged residues in its intracellular domain, indicating that it may be involved in intracellular signaling. Scarf2 is expressed in mouse branchial or pharyngeal arches and mandibular maxillary and urogenital ridge tissues [Anastasio et al, 2010].…”
Section: Discussionmentioning
confidence: 99%
“…These defects in cilia are associated with a range of human diseases, such as primary ciliary dyskinesia, hydrocephalus, polycystic liver and kidney disease, and some forms of retinal degeneration (26). Using WES, mutations that cause ciliopathy diseases were found: Van Den Ende-Gupta, Sensenbrenner, Joubert, Bardet-Biedl syndromes, Leber congenital amaurosis, polycystic kidney disease, primary ciliary dyskinesia (21)(22)(23)(24)(27)(28)(29)(30)(31). Exome sequencing effectively confirmed that the nonsynonymous mutation chr22:19115386 C>T in the SCARF2 gene, which is expressed during development, is responsible for Van Den Ende-Gupta syndrome that affects multi-system (21).…”
Section: Discussionmentioning
confidence: 99%
“…Using WES, mutations that cause ciliopathy diseases were found: Van Den Ende-Gupta, Sensenbrenner, Joubert, Bardet-Biedl syndromes, Leber congenital amaurosis, polycystic kidney disease, primary ciliary dyskinesia (21)(22)(23)(24)(27)(28)(29)(30)(31). Exome sequencing effectively confirmed that the nonsynonymous mutation chr22:19115386 C>T in the SCARF2 gene, which is expressed during development, is responsible for Van Den Ende-Gupta syndrome that affects multi-system (21). Also there were studies where exome sequencing was applied to reveal genes causing Joubert syndrome -a neurological, ciliopathic disorder manifested by psychomotor retardation, hypotonia, and ataxia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation